Society Cultural Approach Model in the Process of Connected Mediation in Indonesia - Indriati Amarini (International Journal of Advanced Science and Technology, 2020)
The paradigm of mediation was developed by the Supreme Court by integrating it into the process of civil proceedings in court. However, the result of the mediation was not optimal. This research aimed at analysing the mediator judge approach method during the mediation process in court. This research used philosophical and conceptual approaches. The data used in this research were the secondary data related to the role of a mediator judge in the court-connected mediation to resolve the dispute. They were collected by using literature studies by searching, exploring, collecting, and analyzing the required data. The data was analyzed by using a qualitative method to result in the conclusion. The research showed that the court mediation was not successful because the mediation settlement in court has not been used as an alternative dispute resolution by society. The judge conducted the mediation process only as a formality in settling civil cases. The approach needs to be taken by the mediator judge is an approach that is appropriate to the culture of local society. This is in line with the judge's obligation to realize the eminent mandate of accommodating legal values in society.